Gulf of Cadiz zooplankton: Community structure, zonation and temporal variation. (July 2020) - Llope, Marcos; de Carvalho-Souza, Gustavo F.; Baldó, Francisco; González-Cabrera, Carmen; Jiménez, María Paz; Licandro, Priscilla; Vilas, César
Highlights: Gulf of Cadiz zooplankton spatio-temporal variation described for the first time. Guadalquivir River makes the difference and determines much of basin zonation. General decrease in the last five years. Abstract: This study provides the first comprehensive description of the Gulf of Cadiz (SW Spain) marine zooplankton community. To do this we compiled information from a number of surveys and monitoring programs carried out in the area over the last 14 years. Using this time-series of quarterly (3 times per year) resolution, we describe their general composition, spatio-temporal variability and relationship with environmental factors. Zooplankton is dominated by copepods (mainly Clausocalanus, Paracalanus, Oncaea and Oithona ), except in warm periods, when outbreaks of cladocerans (mainly Penilia avirostris but also Podon intermedius and Pleopis polyphemoides ) outnumber copepods, accounting for more than 80% of total abundance on occasion. Zooplankton diversity was found to be higher in deeper waters while the density of most taxa (but not their abundance) decreased towards the ocean. On top of this general coast-ocean pattern a north–south gradient could also be distinguished resulting in three distinct zones. In relation to environmental structuring, mesoscale processes, sea surface temperature, winds, river runoff and primary productivity were identified as main factors shaping this zonation. Overall, zooplankton abundance showed a decreasing trend during the study period (2001–2015), caused by a drop of summer abundances, that was mainly driven by cladocerans.